Hubungan Antara Grit Dengan Self- Efficacy Pada Mahasiswa Angkatan 2025 di Universitas Jambi - Angellyca Alexsandra; Aulia Artika; Khansa Ifra Alifah; Beny Rahim; Jelpa Periantalo; Muhammad Ilham; Dinda Agraiza (CV. ITTC INDONESIA, 2026)
Grit is a psychological variable rooted in an individual’s character strength, focusing on the process of achieving long-term success, driven by a strong desire to attain those goals. Meanwhile, self-efficacy refers to an individual’s belief in their ability to handle challenges in order to achieve their goals. The purpose of this study is to examine the relationship between grit and self-efficacy among the 2025 cohort of students at the University of Jambi. This study employs a quantitative approach using a correlational method. The sample consisted of 50 students recruited through an online questionnaire. Data analysis was conducted using Jeffreys’s Amazing Statistics Program. The results indicate that there is no significant relationship between grit and self-efficacy among the 2025 cohort of students at Jambi University.